Basic approach on the protective effects of hesperidin and naringin in Alzheimer's disease - Kusi, Muejgan; Becer, Eda; Vatansever, Hafize Seda (Taylor & Francis Ltd, 2025)
ObjectivesAlzheimer's disease (AD) is a neurodegenerative disease characterized by cognitive impairment. This situation imposes a great burden on individuals, both economically and socially. Today, an effective method for treating the disease and protective approach to tau accumulation has not been developed yet. Studies have been conducted on the effects of hesperidin and naringin flavonoids found in citrus fruits on many diseases.MethodsIn this review, the pathophysiology of AD is defined, and the effects of hesperidin and naringin on these factors are summarized.ResultsStudies have shown that both components may potentially affect AD due to their antioxidative and anti-inflammatory properties. Based on these effects of the components, it has been shown that they may have ameliorative effects on A beta, alpha-synuclein aggregation, tau pathology, and cognitive functions in the pathophysiology of AD.DiscussionThere are studies suggesting that hesperidin and naringin may be effective in the prevention/treatment of AD. When these studies are examined, it is seen that more studies should be conducted on the subject.
Keywords: Alzheimer's disease; hesperidin; naringin; neuroprotective effect; oxidative stress; inflammation; A beta aggregation; antiapoptotic effect